Antimicrobial synergic effect of chitosan with sodium lactate, nisin or potassium sorbate against the bacterial flora of fish - Schelegueda, Laura Inés (2012)
The inhibitory action of sodium lactate (SL), potassium sorbate (PS), nisin and chitosan against representative bacteria of fish spoilage flora (two Pseudomonas strains, Shewanella putrefaciens and Lactobacillus plantarum) and also against Listeria innocua was assessed. Minimum inhibitory and bactericidal concentrations were determined. Antimicrobial interactions seeking for synergistic effects between binary mixtures were evaluated by isobolograms and by the fractional inhibitory concentrations (FIC). To study antimicrobials effects on a food matrix, selected mixtures showing synergistic action were tested in fish homogenates. Most antimicrobials inhibited bacterial growth. Isobolograms and FIC index showed that the combination of antimicrobials with chitosan and the mixture PS-SL exerted a synergistic action. Among them, combinations containing PS were discarded, since the levels needed may have adverse effects on the sensory characteristics of fish. Regarding to fish homogenates, chitosan in combination with SL, achieved the greater reduction of bacterial population, being useful for the preservation of minimally processed fish.